Analisis faktor kejadian wasting pada anak balita 12-59 bulan di Puskesmas Bulili Kota Palu: Studi cross sectional - Hepti Muliyati; Menis Mbali; Hadidja Bando; Riana Pangestu Utami; Opyn Mananta (AcTion: Aceh Nutrition Journal, 2021)
Wasting on children is an important public health problem because of its considerable impact on their health and growth. This problem could lead to iron deficiency which could induce infection disease and probably lower a child’s intelligence as a long-term effect. This study aimed to analyze factors related to wasting on 12-59 months children in Bulili Public Health Center (PHC), Palu City. The analytical descriptive study designed with a cross-sectional approach was applied in this study. One hundred and twenty-one subject was selected from 283 children with purposive sampling technique. Data were analyzed with chi-square and Fisher exact test with significant (p < 0,05). The result showed that most children with low birth weight experienced wasting with a p-value = 0,000. Most of the children from higher-income families did not experience wasting with a p-value = 0,004. Most children who didn’t receive breastfeeding milk did not experience wasting with a p-value = 0,958. This study concluded a correlation between low birth weight and income to wasting, but breastfeeding practice was not related.